Arthur Schnitzler und der Film - Wolf, Claudia (KIT Scientific Publishing, 2006)
The study presents an overview of Arthur Schnitzler's collaborative work with the film industry. His attitude towards the cinema is taken into account and also his perceptions and theoretical reflection on the new medium. In addition to the history of the movies produced during Schnitzler's lifetime on the basis of his literary texts, Schnitzler's own drafts based on his literature works, and finally his screenplays and movie sketches are considered. Based on Schnitzler's own drafts and his comments on the movies, the historical context of Schnitzler, his aesthetic demands, his film technique and his cinematic narrative strategies are reconstructed.